An investigation into the effect of welding current on the plasma arc welding of pure titanium - Kahraman, N.; Taskin, M.; Gulenc, B.; Durgutlu, A. (Redakcia Kovove Materialy, 2010)
In the present study, plasma arc welding method was applied to commercial purity titanium using various welding current values. In order to determine the strength of the resulting joints, tensile tests, impact tests and hardness tests were applied. Additionally, optical microscopy examinations were carried out to determine the interface properties of the joints. The work showed that the highest interface strength was obtained for the specimens joined at 65 A. For all the welding parameters, the hardness test results showed that weld metal gave a higher hardness value than heat affected zone and base metal. The microstructure in welded joint consisted of acicular alpha and twins.
Keywords: plasma arc welding; titanium; welding current